Effectiveness and safety of human placenta hydrolysate injection into subacromial space in patients with shoulder impingement syndrome: a single-blind, randomized trial - Du Hwan Kim; Myung Woo Park; Hyun Iee Shin; Byung Chan Lee; Don-Kyu Kim; Chul-Hyun Cho; Ye-Ji Kim (BMC Musculoskeletal Disorders)
Abstract Background Human placental hydrolysate (hPH) contains anti-inflammatory substances. This study aimed to analyze whether injecting hPH into the subacromial space could reduce pain in patients with shoulder impingement syndrome. Methods This single-blind, randomized controlled study enrolled 50 patients with shoulder impingement syndrome who were randomly assigned to either the hPH or placebo groups. All patients received three ultrasound-guided subacromial space injections of 4 mL hPH or normal saline every week. Outcome measurements included the Visual Analog Scale (VAS) score during daily activity, Shoulder Pain and Disability Index (SPADI), and EuroQoL 5-Dimension 5-Level (EQ-5D-5L) utility index. Patients were followed up for nine weeks after the last injection. Results Significant differences were noted in the VAS (p < 0.001) during daily activity, SPADI total score (p < 0.001), and EQ-5D-5L utility index (p < 0.001) nine weeks after the last injection between the hPH group and placebo group. Significant time effects were observed for all outcome measurements (all p < 0.001) in the hPH group but not in the placebo group. No severe complications, such as local infections or laboratory abnormalities, were reported during this study. Conclusions Subacromial injections showed significant improvement in pain, functional level, and quality of life in patients with shoulder impingement syndrome. Therefore, hPH can be used as an alternative treatment for shoulder impingement syndrome. Trial registration The trial was registered on www.Clinicaltrials.gov (NCT05528705, Registration Date: 06/09/2022).